Extricating short-duration and bold-grained high-yielding soybean genotypes under waterlogging conditions - Akter, Mafruha; Al Mamun, M. Abdullah; Akter, Munny; Baset Mia, M. Abdul; Karim, M. Abdul (Acta Biologica Szegediensis, 2025)
Two experiments were conducted at BSMRAU, Gazipur, during 2021 and 2022 to analyze the effects of waterlogging (WL) on the performance of short-duration, bold-seeded soybean genotypes and assess the impact on seed quality. In 2021, twelve genotypes—BD2334, G00113, G00164, G00064, G00221, BD2331, G00138, G00321, G00058, G00060, G00025, and BU Soybean-1—were evaluated under control and WL conditions. In 2022, five selected genotypes (BD2334, G00164, BD2331, G00060, and BU Soybean-1) were assessed. Plants were subjected to WL stress for seven days in 2021 and five days in 2022 during the pod formation stage. A split-plot design with three replications was employed. Waterlogging stress significantly reduced yield, yield attributes, SPAD value, photosynthesis rate, photosynthetic pigments, transpiration rate, stomatal conductance, germination rate, and early seedling growth. However, it increased electrolyte leakage in seeds as well as proline and malondialdehyde content in leaves. Waterlogged plants matured earlier than their respective control plants. Genotypic differences in WL tolerance were evident, with BD2334, G00164, G00221, and BD2331 exhibiting better yield performance under WL stress. Genotype G00060 demonstrated higher tolerance to WL based on specific physiological parameters. These findings suggest that these genotypes may be suitable for further field evaluation to identify WL-tolerant soybean varieties.